THE IMPACT OF SOCIAL MEDIA ON YOUTH BEHAVIOR - Sabirbaeva Guljayna Saparbay qizi,; Jumabaeva Dinara Orazbay qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract   This article explores the impact of social media on youth behavior in the modern digital world. With the rapid growth of internet technologies, social media platforms have become an essential part of young people’s daily lives. The study analyzes both the  positive  and  negative  influences  of  social  media,  focusing  on  communication, education,  mental  health,  and  lifestyle  changes.  While  social  media  provides opportunities for learning, creativity, and global interaction, it also presents risks such as  addiction,  cyberbullying,  and  decreased  academic  performance.  The  article highlights the importance of balanced and responsible use of social media to ensure healthy development among youth.